Distributed functional interval observers for nonlinear interconnected systems with time-delays and additive disturbances - Dinh Cong Huong; Van Thanh Huynh; Hieu Trinh (My University, 2021)
Distributed functional interval observers for nonlinear interconnected systems with time-delays and additive disturbances
Keywords: Distributed observers; Nonlinear interconnected; Additive disturbances